Impact of combined versus single-mode training programs based on drop jump and specific multidirectional repeated sprint on bio-motor ability adaptations: a parallel study design in professional basketball players - Brini, S.; Boullosa, D.; Calleja-González, J.; van den Hoek, D. J.; Nobari, H.; Clemente, F. M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Jumping and specific multidirectional repeated sprint ability are important in basketball. The objective of this study was to assess the contributions of 8-week combined versus single-mode training programs based on drop jump (DJ) and specific multidirectional repeated sprint (MRSA) on repeated sprint ability performances, body balance and lower limbs power in male professional basketball players.